One Course, Two Approaches:: ITA Educators’ Diverging Ideologies - Anderson, Roger (Journal of International Students, 2024)
International Teaching Assistants (ITA’s) are critical to North American campuses. While studies have explored their experiences in through ITA training courses, research has overlooked the experiences of ITA educators. A multiple case study examined three ITA educators’ ideologies, gathering data from two interviews -one  stimulated recall using classroom observations fieldnotes, syllabi, assignments, and feedback. Two incompatible sets of ideologies were found being implemented: one oriented learners to undergraduate classrooms, and one towards required language testing. Employment frustrations and cynicism impacted each instructor. Findings highlight the ethical complexities of language teaching. Programs must scrutinize the role of language testing within ITA training and examination support available to ITA educators. This novel study, focusing on the often-overlooked ITA educator, situated their ideologies adjacent to their identities, and using methodological innovations. Future work is needed to elucidate how ITA educators’ identities and ideologies impact ITA’s learning experience and academic or professional trajectories.